Diversity and Inclusion Practices among Different Cultures - Borkowska, Marta (Facets of Managing in Cross-Cultural Diversity, 2021)
The aim of this chapter is to analyse diversity and inclusion (D&I) practices from the perspective of different cultures and verify if approaches towards those concepts are common or contain disparities. According to a literature analysis, approaches towards D&I vary significantly depending on the culture, mostly due to a country’s location (Western vs. Eastern), and history and values by which a nation is driven. Research conducted in an international IT company, on the contrary, shows no differences in D&I practices among cultures. Lack of diversification may be a result of the necessity to adapt to a constantly changing business world and requirements imposed on all units of an organisation to follow one coherent strategy in terms of D&I. Research limitations as well as the need for a further analysis in order to fully investigate the subject are also discussed.